Copper paste, electrode, solar cell, and photovoltaic module

CN122968032APending Publication Date: 2026-10-23LONGI GREEN ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611179122.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0003]铜因为具有优异的导电性和较低的成本成为研究热点,但是因铜易被氧化,需要在低温下制备电极,而在低温下因烧结温度不足导致铜浆中铜颗粒之间的接触不够紧密和铜颗粒与基底之间的附着力不足,导致制备的铜电极具有较大的电阻和不稳定性,难以提升由此形成的太阳能电池的效率和功率

Benefits of technology

[0034]根据本申请实施例的铜浆料,通过使用微米级的第一导电铜颗粒形成后续烧结得到的铜电极的骨架,将纳米级的第二导电铜颗粒填充在第一导电铜颗粒形成的骨架内,能够充分地在铜电极中填充到第一导电铜颗粒难以进入的微小空隙中,并连接相邻的第一导电铜颗粒,进而通过第一导电铜颗粒和第二导电铜颗粒之间的复配提高导电铜颗粒在铜电极内的堆积紧密度,显著增加导电通路的数量,进而降低接触电阻。并且,作为导电骨架的微米级的第一导电铜颗粒的形状为多面体,相较于球形颗粒具有与第二导电铜颗粒更多的接触点和接触面,扩展了导电界面,与纳米级的第二导电铜颗粒堆积成铜电极时,能够显著降低铜电极内导电网络的渗流阈值,为电子传输提供了较多通道。粒径为50~300nm的第二导电铜颗粒具有较高的流动性,能提高铜浆料的可印刷性,并且提高后续烧结形成的铜电极应对形变的稳定性,进而增强后续铜电极与电池基底之间的连接强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968032A_ABST
    Figure CN122968032A_ABST
Patent Text Reader

Abstract

The application provides a kind of copper paste, electrode, solar cell and photovoltaic module, belongs to the technical field of conductive material.The copper paste includes: copper powder and dispersion medium;The copper powder includes a plurality of first conductive copper particles and a plurality of second conductive copper particles;The average particle size of the plurality of first conductive copper particles is 1~10 μm, the average particle size of the plurality of second conductive copper particles is 50~300 nm, and the shape of the first conductive copper particle is polyhedron.Such as by introducing larger first conductive copper particles to construct the skeleton to maintain the fluidity of copper paste and the initial structural strength of subsequent printed copper electrode, and compound smaller second conductive copper particles are filled in the gap of first conductive copper particles, significantly improve the packing density of conductive copper particles in the subsequent formed copper electrode, reduce the contact resistance, the specific shape of the first conductive copper particle can significantly reduce the percolation threshold of the conductive network in the copper electrode, further expand the conductive interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of conductive materials technology, specifically to a copper paste, an electrode, a solar cell, and a photovoltaic module. Background Technology

[0002] Photovoltaic power generation is an environmentally friendly renewable energy technology that converts light energy into electrical energy using solar cells. Conductive silver paste is widely used in solar cells to collect and transport photogenerated charge carriers. However, as the cost of metallic silver continues to rise, attempts are being made to use other metals to replace it.

[0003] Copper has become a research hotspot due to its excellent conductivity and low cost. However, because copper is easily oxidized, electrodes need to be prepared at low temperatures. At low temperatures, insufficient sintering temperature leads to insufficient contact between copper particles in the copper paste and insufficient adhesion between copper particles and the substrate. This results in copper electrodes with high resistance and instability, making it difficult to improve the efficiency and power of the resulting solar cells. Summary of the Invention

[0004] In view of this, in order to at least partially solve the aforementioned technical problems, this application provides a copper paste, an electrode, a solar cell, and a photovoltaic module.

[0005] According to one embodiment of this application, a copper paste is provided, comprising: copper powder and a dispersion medium; the copper powder includes a plurality of first conductive copper particles and a plurality of second conductive copper particles; the average particle size of the plurality of first conductive copper particles is 1~10μm, the average particle size of the plurality of second conductive copper particles is 50~300nm, and the shape of the first conductive copper particles is a polyhedron.

[0006] In some embodiments, the average particle size of the plurality of first conductive copper particles is 2 to 5 μm.

[0007] In some embodiments, the first conductive copper particle is shaped as an irregular polyhedron.

[0008] In some embodiments, the ratio of the maximum distance to the minimum distance between the two opposite ends of the first conductive copper particle is (1~3):1.

[0009] In some embodiments, at least one surface of the first conductive copper particle is non-planar.

[0010] In some implementations, at least one surface has a first texture structure.

[0011] In some embodiments, the second conductive copper particle is a sphere or a spherical-like particle.

[0012] In some embodiments, the D of the second conductive copper particle 95 Particle size and D50 The ratio of particle size to particle size is <3.

[0013] In some embodiments, the surface of the second conductive copper particle has a second textured structure.

[0014] In some embodiments, the first conductive copper particle and / or the second conductive copper particle are composed of elemental copper.

[0015] In some embodiments, the surfaces of the first conductive copper particle and / or the second conductive copper particle are sequentially coated with a first coating layer and a second coating layer from the inside out. The first coating layer is composed of copper oxide, and the second coating layer is composed of at least one of organic matter, copper hydride, or hypophosphite compounds.

[0016] In some embodiments, the thickness of the first coating layer and / or the second coating layer is 1 to 50 nm.

[0017] In some embodiments, the thickness of the first coating layer and / or the second coating layer is 1 to 20 nm.

[0018] In some embodiments, the second conductive copper particle is composed of copper hydride.

[0019] In some embodiments, the dispersion medium includes a resin, a curing agent, a dispersant, and a solvent.

[0020] In some embodiments, the resin is a thermosetting resin.

[0021] In some embodiments, the resin is selected from at least one of phenolic resin, epoxy resin, polyester resin, vinyl resin, phthalate resin, oligonucleotide acrylate resin, xylene resin, bismuth triazine resin, polyurethane, melamine resin, silicone resin, acrylic resin, oxetane resin, and oxazine resin.

[0022] In some embodiments, the resin content in the copper paste is 1-15% by mass.

[0023] In some embodiments, the mass ratio of the first conductive copper particle to the second conductive copper particle is (0.5~10):1.

[0024] According to another embodiment of this application, an electrode is provided, including a transmission electrode, which is a copper electrode. The copper electrode includes a plurality of third conductive copper particles and a plurality of fourth conductive copper particles. The average particle size of the plurality of third conductive copper particles is 1~10μm, and the shape of the third conductive copper particles is polyhedral. The average particle size of the plurality of fourth conductive copper particles is 50~400nm. At least some of the adjacent fourth conductive copper particles have an overlap portion, and the adjacent fourth conductive copper particles are connected through the overlap portion.

[0025] In some embodiments, the average particle size of the third conductive copper particles is 1~5μm.

[0026] In some implementations, adjacent third and / or fourth conductive copper particles are connected by surface contact or body contact.

[0027] In some embodiments, the surface of the third conductive copper particle has at least one first microstructure, the first microstructure being recessed toward the interior of the third conductive copper particle, and a portion of the fourth conductive copper particle is located within the first microstructure.

[0028] In some embodiments, the copper electrode is prepared using the copper paste described above.

[0029] In some embodiments, the electrode further includes a contact electrode, which is electrically connected to the transmission electrode; the material of the contact electrode includes at least one of metal, metal oxide, metal nitride, metal carbide, metal sulfide, or conductive carbon material.

[0030] In some embodiments, the material of the contact electrode includes metallic silver, and the contact electrode includes a plurality of first silver particles and a plurality of second silver particles, wherein the average particle size of the plurality of first silver particles is 1 to 10 μm, and the average particle size of the plurality of second silver particles is 0.05 to 0.5 μm.

[0031] According to another embodiment of this application, a solar cell is provided, including a cell body and electrodes, the electrodes being located on at least one surface of the cell body, the electrodes including the electrodes described above.

[0032] In some embodiments, the solar cell is selected from any one of a back contact cell, a heterojunction cell, or a tunnel oxide passivated contact cell.

[0033] According to another embodiment of this application, a photovoltaic module is provided, including a plurality of solar cells as described above, and a plurality of electrical connection lines electrically connecting adjacent solar cells.

[0034] According to the copper paste of this application embodiment, by using micron-sized first conductive copper particles to form the framework of the copper electrode obtained by subsequent sintering, and filling the framework formed by the first conductive copper particles with nano-sized second conductive copper particles, it is possible to fully fill the tiny gaps in the copper electrode that are difficult for the first conductive copper particles to enter, and connect adjacent first conductive copper particles. This, in turn, improves the packing density of the conductive copper particles in the copper electrode through the combination of the first and second conductive copper particles, significantly increasing the number of conductive pathways and thus reducing contact resistance. Furthermore, the micron-sized first conductive copper particles, which form the conductive framework, are polyhedral in shape, having more contact points and contact surfaces with the second conductive copper particles compared to spherical particles, thus expanding the conductive interface. When stacked with the nano-sized second conductive copper particles to form a copper electrode, this significantly reduces the percolation threshold of the conductive network within the copper electrode, providing more channels for electron transport. The second conductive copper particles, with a particle size of 50~300nm, have high fluidity, improving the printability of the copper paste and enhancing the stability of the copper electrode formed by subsequent sintering to withstand deformation, thereby strengthening the connection strength between the subsequent copper electrode and the battery substrate. Attached Figure Description

[0035] The above and other objects, features and advantages of this application will become clearer from the following description of embodiments of this application with reference to the accompanying drawings.

[0036] Figure 1 This paper shows a scanning electron microscope image of a cross section of air-dried copper paste according to an embodiment of this application;

[0037] Figure 2 A scanning electron microscope image of a cross section of air-dried copper paste according to another embodiment of this application is shown;

[0038] Figure 3 This paper shows a scanning electron microscope image of a cross section of air-dried copper paste according to another embodiment of the present application;

[0039] Figure 4 A scanning electron microscope image of a cross-section of a copper electrode according to an embodiment of this application is shown;

[0040] Figure 5 A scanning electron microscope image of a cross-section of a copper electrode according to another embodiment of this application is shown;

[0041] Figure 6 A partial transmission electron microscope (TEM) image of a cross-section of a copper electrode according to an embodiment of this application is shown.

[0042] Figure 7 It shows the relationship with Figure 6 Elemental analysis diagrams at the same locations;

[0043] Figure 8 A top-view scanning electron microscope image of a copper electrode according to an embodiment of this application is shown;

[0044] Figure 9 A scanning electron microscope image of a cross-section of a copper electrode according to another embodiment of this application is shown;

[0045] Figure 10 A transmission electron microscope (TEM) image of a cross-section of a copper electrode according to an embodiment of this application is shown.

[0046] Figure 11 It shows the relationship with Figure 10 Elemental analysis diagrams at the same locations;

[0047] Figure 12 An elemental analysis diagram of a cross-section of the contact electrode according to an embodiment of this application is shown;

[0048] Figure 13 A schematic diagram of the structure of a solar cell according to an embodiment of this application is shown;

[0049] Figure 14 A schematic diagram of the structure of a solar cell according to another embodiment of this application is shown.

[0050] The meanings of the reference numerals in the above figures are as follows:

[0051] 1. First conductive copper particle; 11. First texture structure; 2. Second conductive copper particle; 12. Second texture structure; 3. Third conductive copper particle; 31. First microstructure; 4. Fourth conductive copper particle; 5. Overlapping part; L1. Maximum distance; L2. Minimum distance;

[0052] 100, Substrate; 101a, First surface; 101b, Second surface; 1021, First doped conductive layer; 1022, Second doped conductive layer; 1031, First interface passivation layer; 1032, Second interface passivation layer; 1041, First passivation or antireflection layer; 1042, Second passivation or antireflection layer; 210, First electrode; 220, Second electrode; 230, First silver electrode; 240, Second silver electrode. Detailed Implementation

[0053] The embodiments of this application will now be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of this application. In the following detailed description, numerous specific details are set forth to provide a thorough understanding of the embodiments of this application for ease of explanation. However, it will be apparent that one or more embodiments may be implemented without these specific details. Furthermore, descriptions of well-known structures and technologies are omitted in the following description to avoid unnecessarily obscuring the concepts of this application.

[0054] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of this application. The term "comprising" as used herein indicates the presence of features, steps, or operations, but does not exclude the presence or addition of one or more other features.

[0055] When using expressions such as "at least one of A, B, and C," the expression should generally be interpreted in accordance with the meaning commonly understood by a person skilled in the art (e.g., "a system having at least one of A, B, and C" should include, but is not limited to, systems having A alone, having B alone, having C alone, having A and B, having A and C, having B and C, and / or having A, B, and C, etc.). When using expressions such as "at least one of A, B, or C," the expression should generally be interpreted in accordance with the meaning commonly understood by a person skilled in the art (e.g., "a system having at least one of A, B, or C" should include, but is not limited to, systems having A alone, having B alone, having C alone, having A and B, having A and C, having B and C, and / or having A, B, and C, etc.).

[0056] In this application, the relative position between two components (e.g., a membrane or region), as referred to by terms such as "above," "on," or "above," can mean that the two components are in direct contact or that they are not in direct contact. Similarly, the relative position between two components, as referred to by terms such as "below," "under," or "below," can mean that the two components are in direct contact or that they are not in direct contact. For example, when one component (e.g., a membrane or region) is referred to as "on another component," it can be directly on the other component, or there may be other components between them. On the other hand, when a component is referred to as "directly on another component," there are no components between them. Furthermore, when one component is referred to as "on another component," the two components have a vertical relationship in the planar view, and this component can be above or below the other component, thus this vertical relationship depends on the orientation of the device.

[0057] Solar cells are widely used due to their mature technology and high photoelectric conversion efficiency. Currently, the electrodes in solar cells are usually made of silver or silver-plated copper. Because silver is expensive, the overall cost of solar cells is high. Although silver-plated copper is cheaper than silver, the reduction is limited. Therefore, it is necessary to find a way to reduce the cost of solar cells while maintaining high conductivity.

[0058] In realizing the concept of this application, it was discovered that by using conductive copper particles of different particle sizes, the first conductive copper particles with larger particle sizes are used to construct the skeleton to provide the initial structural strength of the printed copper electrode, and the second conductive copper particles with smaller particle sizes are compounded to fill the gaps between the first conductive copper particles, thereby increasing the overall packing density of the copper powder. Furthermore, by utilizing the polyhedral shape of the first conductive copper particles, the contact points and contact surfaces with the second conductive copper particles are increased, further expanding the conductive interface and increasing the electron transport channels. In addition, the second conductive copper particles can act as an auxiliary binder when the copper electrode is subsequently sintered and cured to form the copper electrode, thereby improving the adhesion between the copper electrode and the battery substrate.

[0059] Specifically, according to one aspect of this application, a copper paste is provided, comprising: copper powder and a dispersion medium, wherein the copper powder is dispersed in the dispersion medium.

[0060] In this process, copper powder is the conductive phase of the copper paste, providing conductive particles for the paste. The dispersion medium is the dispersed phase, used to disperse the copper powder.

[0061] In one specific embodiment, the copper powder comprises a plurality of first conductive copper particles 1 and a plurality of second conductive copper particles 2; the average particle size of the plurality of first conductive copper particles 1 is 1~10μm, the average particle size of the plurality of second conductive copper particles 2 is 50~300nm, and the shape of the first conductive copper particles 1 is polyhedral. For example Figures 1-2 As shown. Figure 1 This paper shows a scanning electron microscope image of a cross section of air-dried copper paste according to an embodiment of this application; Figure 2 A scanning electron microscope image of a cross section of air-dried copper paste according to another embodiment of this application is shown.

[0062] According to embodiments of this application, the polyhedral-shaped first conductive copper particles 1 provide a higher probability of surface contact. At the same volume fraction as spheres, the polyhedral shape is more conducive to constructing interconnected paths and reducing the percolation threshold. By utilizing the polyhedral-shaped first conductive copper particles 1 to construct the basic framework of the copper paste, and filling the gaps formed by the stacking of multiple first conductive copper particles 1 with relatively smaller second conductive copper particles 2, and connecting adjacent first conductive copper particles 1, it helps to increase the packing density, thereby reducing the porosity and improving the compactness of the subsequently formed copper electrode, thus increasing the number of conductive pathways and significantly reducing contact resistance. The smaller-sized second conductive copper particles 2 preferentially melt during subsequent sintering and solidification, assisting in firmly connecting the larger first conductive copper particles 1 to the battery substrate, thereby improving adhesion. Furthermore, the gradation of micron-level and nano-level copper particles allows the copper paste to exhibit a superior thixotropic index, ensuring the printable rheological properties of the copper paste. This ensures both high aspect ratio and fine linewidth printing, while avoiding sagging during static placement.

[0063] In this application, the term "polyhedron" can be understood as a particle having multiple straight or slightly curved facets, sharp edges and apex angles, and having a three-dimensional configuration, excluding spheres or quasi-spheres.

[0064] In this application, the term "percolation threshold" can be understood as the minimum volume fraction required for a conductive paste to begin forming a connected conductive network in an insulating medium, causing the conductive material to abruptly transform from an insulator into a conductor.

[0065] It should be noted that the average particle size of the conductive copper particles can be measured using a scanning electron microscope (SEM). Ten different regions of the test sample are photographed, resulting in ten images. Then, the particle size of any ten first conductive copper particles 1 or second conductive copper particles 2 observed in each image is measured. The arithmetic mean of the particle sizes of the same type of conductive copper particles in the sample is then calculated; this is the average particle size. It is understood that the above method is merely exemplary, and the number of photographed areas and / or conductive copper particles can be appropriately reduced or increased based on actual conditions. For irregularly shaped polyhedra, the distances between the opposite ends of the copper particles in multiple directions can be measured, and the average value is then taken to obtain the average particle size.

[0066] It should be noted that the first conductive copper particles can be purchased commercially or prepared by chemical reduction. During the preparation process, the morphology and particle size of the first conductive copper particles are controlled by adding a surface protectant. For example, the first conductive copper particles are prepared by the reduction reaction of copper salts with ascorbic acid in the presence of a surface protectant. The surface protectant can be a substance commonly used in the preparation of nanomaterials, such as at least one of gum arabic, gelatin, sodium hexametaphosphate, polyvinyl alcohol, polyvinylpyrrolidone, polyethylene glycol, sodium citrate, tartaric acid, maleic acid, benzotriazole, sodium citrate, cetyltrimethylammonium bromide, and disodium ethylenediaminetetraacetate. The second conductive copper particles can be prepared by physical vapor deposition (PVD), gas atomization, water atomization, or chemical reduction under normal pressure.

[0067] Compared to the sheet-like conductive copper particles in the prior art, the first conductive copper particle with a polyhedral shape in this application omits the pressing step, thereby reducing the preparation cost of the first conductive copper particle and thus reducing the overall production cost of copper powder and copper paste.

[0068] Optionally, the average particle size of the first conductive copper particle 1 can be, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, or a range consisting of any two of the above values.

[0069] Optionally, the average particle size of the second conductive copper particle 2 can be, for example, 50nm, 80nm, 110nm, 140nm, 170nm, 200nm, 230nm, 260nm, 280nm or 300nm, or a range consisting of any two of the above values.

[0070] In some embodiments, the average particle size of the first conductive copper particle 1 is 2~5μm. Based on the more uniform particle size distribution, it is more beneficial to improve the packing density of the conductive copper particles in the copper electrode together with the second conductive copper particle 2, thereby further reducing the contact resistance.

[0071] In some embodiments, the first conductive copper particle 1 is shaped as an irregular polyhedron. In this application, "irregular polyhedron" can be understood as a particle with an anisotropic three-dimensional configuration. The surfaces of the irregular polyhedron are not uniform in size, the lengths of the edges are not uniform, and it does not have geometric symmetry.

[0072] The first conductive copper particle 1, with its irregular polyhedral shape, has a variety of unequal edges and in-plane angles, resulting in a higher specific surface area and a greater number of contact points. In the copper electrode, the first conductive particle 1 and the second conductive particle form a variety of contact methods, including point contact, line contact, surface contact, or volume contact, thereby significantly reducing the percolation threshold and forming a more efficient and stable conductive network.

[0073] In some implementations, reference Figure 1 As shown, the ratio of the maximum distance L1 to the minimum distance L2 between the two opposite ends of the first conductive copper particle 1 is (1~3):1. This facilitates the formation of more contact points and contact surfaces with the second conductive copper particle 2, further reducing the contact resistance.

[0074] Specifically, through image capture, the maximum distance can be understood as the maximum linear dimension of the first conductive copper particle 1 in any direction, that is, the distance from which parallel tangents can be drawn at the two farthest vertices of the first conductive copper particle 1. For example... Figure 1 The maximum distance L1; the minimum distance can be understood as the minimum linear dimension of the first conductive copper particle 1 in any direction, that is, the minimum distance at which parallel tangents can be drawn between the two closest vertices of the first conductive copper particle 1, for example. Figure 1 The minimum distance L2 in the middle.

[0075] Optionally, the ratio of the maximum distance L1 to the minimum distance L2 between the two opposite ends of the first conductive copper particle 1 can be, for example, 1:1, 1.5:1, 2:1, 2.5:1 or 3:1, or a range consisting of any two of the above values.

[0076] In some embodiments, at least one surface of the first conductive copper particle 1 is non-planar.

[0077] In some further embodiments, at least one surface has a first texture structure, which can be understood as a rough surface. The rough surface may have steps, protrusions on the surface, pits pointing into the interior of the first conductive copper particle 1, etc. Figure 3 A scanning electron microscope (SEM) image of a cross-section of air-dried copper paste according to another embodiment of this application is shown. Figure 3 As shown, this increases the specific surface area of ​​the first conductive copper particle 1, resulting in more contact points with the second conductive copper particle 2. When the edges and steps of the non-planar surfaces of adjacent first conductive copper particles 1 and / or second conductive copper particles 2 overlap with adjacent conductive copper particles, line contact or partial surface contact is more easily formed, thereby increasing the effective conductive contact area and further reducing the contact resistance of the resulting copper electrode. In addition, the non-planar surface of the first conductive copper particle 1 helps to form an anchoring structure with the surrounding resin curing network or battery substrate during subsequent sintering and curing, strengthening the bonding strength and improving the interfacial bonding strength.

[0078] In some embodiments, the second conductive copper particle 2 is a sphere or a quasi-sphere. A sphere can be understood as a three-dimensional sphere with geometric symmetry, equidistant from any point on the surface to the center, and with an aspect ratio of 1. A quasi-sphere can be understood as a particle that appears approximately spherical under a microscopic electron microscope, allowing for a certain degree of slight deformation, such as an ellipsoid, oblate spheroid, or with some surface undulations. The aspect ratio of the quasi-sphere can be greater than or equal to 1 and less than or equal to 1.2. The ratio of the projected area of ​​the quasi-sphere second conductive copper particle 2 on the substrate to the area of ​​a circle with the same circumference is greater than or equal to 0.85.

[0079] It should be noted that this application constructs a composite of micron-sized irregular polyhedral first conductive copper particles 1 and nano-sized spherical or near-spherical second conductive copper particles 2. The second conductive copper particles 2 significantly improve the printability of the copper paste and exhibit good viscosity recovery after printing, preventing sagging and facilitating the printing of copper electrodes with finer linewidths, thus improving the stability of the copper electrode to deformation. Before sintering and curing, the second conductive copper particles 2 can easily embed into the pits and / or gaps on the surface of the first conductive copper particles 1, further increasing the packing density of the entire copper paste system, reducing the porosity inside the copper electrode after sintering, thereby hindering the diffusion of oxygen along the pores and improving the oxidation resistance of the copper electrode. In some embodiments, the D of the second conductive copper particles 2... 95 Particle size and D 50 The particle size ratio is <3. This can be understood as D. 95The particle size refers to the particle size corresponding to 95% of the volume distribution in the sample. In other words, 95% of the second conductive copper particles 2 in the sample have a particle size smaller than the aforementioned value, and 5% of the second conductive copper particles 2 have a particle size larger than the aforementioned value. D 50 Particle size refers to the median particle size, which is the particle size that corresponds to when the cumulative volume distribution in the sample reaches 50%.

[0080] A ratio of less than 3 indicates that the second conductive copper particles 2 have a narrow particle size distribution and high monodispersity. During sintering and solidification to prepare the copper electrode, the relatively uniform particle size allows the second conductive copper particles 2 to melt synchronously after heating, which helps to promote the formation of uniform and dense sintering necks between adjacent second conductive copper particles 2. The sintering neck can be understood as the fusion connection region or connecting bridge formed during the sintering process of the contact area of ​​adjacent conductive copper particles, shortening the sintering time and further reducing the contact resistance. The narrow distribution of the second conductive copper particles 2 makes the viscosity of the copper paste more stable, optimizes the rheology, and provides material preparation for the fine printing of the copper electrode. Simultaneously, during the subsequent solidification and sintering of the copper paste into the copper electrode, sintering necks can be formed uniformly and synchronously, reducing shrinkage stress and contributing to the formation of a uniform and dense three-dimensional conductive network after sintering. It also shortens the sintering time, reduces the degree of oxidation of the second conductive copper particles 2 during air sintering, and achieves lower resistivity and higher mechanical strength. In this application, D 95 Particle size and D 50 Particle size can be measured using a laser particle size analyzer or a scanning electron microscope, which will not be elaborated here.

[0081] In some embodiments, the surface of the second conductive copper particle 2 has a second textured structure. For example... Figure 3 As shown, the second texture structure can be understood as the surface of the second conductive copper particle 2 having slight undulations or being relatively rough. This helps to locally increase the specific surface area of ​​the second conductive copper particle 2, resulting in more contact points or contact surfaces between it and adjacent second conductive copper particles 2 and / or first conductive copper particles 1. During subsequent sintering to prepare the copper electrode, this is more conducive to forming more sintering necks, thereby improving the density and conductivity of the copper electrode prepared in this way.

[0082] In some embodiments, the first conductive copper particle 1 is composed of elemental copper, thus ensuring superior conductivity.

[0083] In some embodiments, the second conductive copper particle 2 is composed of elemental copper or copper hydride. When the second conductive copper particle 2 is composed of elemental copper, it provides superior conductivity. When the second conductive copper particle 2 is composed of copper hydride, its reducing properties enable the formation of highly active nano-copper particles during subsequent sintering and curing. These nano-copper particles rapidly sinter or fuse with the surfaces of adjacent conductive copper particles, forming an effective sintering neck. Simultaneously, the reducing atmosphere prevents undesirable oxidation during sintering, further enhancing the stability of the copper paste and its oxidation resistance after subsequent sintering and curing.

[0084] In some embodiments, the mass ratio of the first conductive copper particle 1 to the second conductive copper particle 2 is (0.5~10):1. This configuration, by adjusting the mass ratio of the first conductive copper particle 1 to the second conductive copper particle 2 in the copper paste, allows the first conductive copper particle 1 and the second conductive copper particle 2 to be densely packed, further reducing the resistance of the resulting copper electrode and improving its conductivity.

[0085] Optionally, the mass ratio of the first conductive copper particle 1 and the second conductive copper particle 2 can be, for example, 0.5:1, 1:1, 1.5:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1, or a range consisting of any two of the above ratios.

[0086] Preferably, the mass ratio of the first conductive copper particle 1 to the second conductive copper particle 2 is (1~5):1.

[0087] In some embodiments, the surface of the first conductive copper particle 1 or the second conductive particle 2 is sequentially coated with a first coating layer and a second coating layer from the inside out. The first coating layer is composed of copper oxide, and the second coating layer is composed of organic matter. The first coating layer can be understood as a copper oxide layer formed by the natural oxidation of the first conductive copper particle 1 or the second conductive particle 2 after being placed in air or coming into contact with oxygen in the environment. The composition of the copper oxide layer here can be copper oxide and / or cuprous oxide, which is not particularly limited in this application. The second coating layer can physically isolate oxygen from contacting the copper surface, isolate the first conductive copper particle 1 or the second conductive particle 2 from contact with external oxygen and moisture, inhibit the generation of oxidation reaction, and thus improve the stability of the first conductive copper particle 1 in a humid and hot environment.

[0088] The end groups of the main chain or branches of the organic coating agent used in the second coating layer can be selected from at least one group selected from amino, amide, mercapto, carboxyl, hydroxyl, carbonyl, thioether, and etheroxy groups, and the number of carbon atoms in the organic coating agent can be 1 to 50.

[0089] In a further embodiment, the organic coating agent containing an amine or amide group may be, for example, octylamine, decylamine, dodecylamine, tetradecylamine, hexadecylamine, octadecylamine, oleylamine, benzylamine, octadecamide, oleamide, etc., and these compounds may be used alone or in combination of two or more.

[0090] In a further embodiment, the organic coating agent containing thiol or thioether group may be, for example, decanethiol, dodecanethiol, trimethylbenzyl mercaptan, butylbenzyl mercaptan, dihexyl sulfide, etc., and these compounds may be used alone or in combination of two or more.

[0091] In a further embodiment, the organic coating agent containing hydroxyl, carboxyl, carbonyl and etheroxy groups can be, for example, dodecanediol, hexadecanediol, dodecanoic acid, octadecanoic acid, oleic acid, formic acid, linoleic acid, linolenic acid, dodecanedione, dibenzoylmethane, ethylene glycol monodecyl ether, diethylene glycol monodecyl ether, triethylene glycol monodecyl ether, tetraethylene glycol monodecyl ether, ethylene glycol monododecyl ether, diethylene glycol monododecyl ether, triethylene glycol monododecyl ether, tetraethylene glycol monododecyl ether, ethylene glycol monohexadecyl ether, diethylene glycol monohexadecyl ether, etc. These compounds can be used alone or in combination of two or more.

[0092] In some embodiments, when the second conductive copper particle 2 is copper hydride, the surface of the second conductive copper particle 2 may not have a coating layer due to the superior oxidation resistance of copper hydride itself.

[0093] In other embodiments, the surface of the first conductive copper particle 1 or the second conductive particle 2 is sequentially coated with a first coating layer and a second coating layer from the inside out. The first coating layer is composed of copper oxide, and the second coating layer is composed of copper hydride or a hypophosphite compound. The first coating layer can be understood as a copper oxide layer formed by the natural oxidation of the first conductive particle 1 or the second conductive copper particle 2 in air. The composition of the copper oxide layer here can be copper oxide or cuprous oxide, which is not particularly limited in this application. The copper hydride in the second coating layer can decompose to form metallic copper during sintering and solidification, or the copper oxide in the first coating layer can react with the hypophosphite compound in the second coating layer to form copper hydride, which then decomposes into metallic copper during sintering and solidification. Since the decomposition of copper hydride produces reducing gas, it can reduce the copper oxide on the surface of the first conductive particle 1 or the second conductive copper particle 2 and effectively inhibit the oxidation of the first conductive copper particle 1 and the second conductive copper particle 2, thereby improving the conductivity and stability of the copper electrode.

[0094] In some implementations, the thickness of the first coating layer is 1 to 50 nm.

[0095] Optionally, the thickness of the first coating layer may be, for example, 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm, or a range consisting of any two of the above values.

[0096] Preferably, the thickness of the first coating layer is 1-30 nm. A smaller thickness of the first coating layer results in a lower surface oxide layer on the surface of the first conductive copper particle 1 or the second conductive copper particle 2, thereby improving the conductivity of the first conductive copper particle 1 or the second conductive copper particle 2.

[0097] In some implementations, the thickness of the second coating layer is 1~50 nm.

[0098] Optionally, the thickness of the second coating layer may be, for example, 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm, or a range consisting of any two of the above values.

[0099] In some further embodiments, the thickness of the second coating layer of the second conductive copper particle 2 is 1~20 nm. This not only provides effective protection for the internal elemental copper, preventing oxidation, but also ensures superior conductivity.

[0100] In some embodiments, when the surface of either the first conductive copper particle 1 or the second conductive copper particle 2 includes a first coating layer and a second coating layer, the surface of the other conductive copper particle may only include the first coating layer or only include the second coating layer. In this case, the chemical composition and thickness of the first or second coating layer of the two conductive copper particles may be the same or different. For example, when the surface of the first conductive copper particle 1 has both a first coating layer and a second coating layer, and the second conductive copper particle 2 only includes the second coating layer, the composition of the second coating layer is preferably copper hydride. When the surface of the second conductive copper particle 2 includes both a first coating layer and a second coating layer, and the first conductive copper particle 2 only includes the first coating layer, the composition of the first coating layer is preferably copper hydride.

[0101] It should be noted that the second coating layer of the first conductive copper particle 1 and / or the second conductive copper particle 2 can be obtained by physical adsorption or chemical reaction of the first conductive copper particle 1 or the second conductive copper particle 2 with the compound forming the second coating layer in solution. When the second coating layer is an organic compound or a hypophosphite compound, the organic compound or hypophosphite compound is adsorbed onto the outside of the first coating layer through physical mixing. When the second coating layer is copper hydride, copper hydride, i.e., the second coating layer, is formed on the surface of the conductive copper particles by the reaction of the copper oxide on the surface of the first conductive copper particle 1 or the second conductive copper particle 2 with the hypophosphite compound in solution. In this application, the hypophosphite compound can be, for example, a hypophosphite ester.

[0102] In some embodiments, the dispersion medium includes a resin. After the copper paste is sintered and cured, the resin forms a continuous phase, which can encapsulate and bond the first conductive copper particles 1 and the second conductive copper particles 2 of different particle sizes into a whole. The addition of resin can give the copper paste higher mechanical strength and better adhesion to the subsequent battery substrate, improve peel strength, and enhance the durability and service life of the copper electrode.

[0103] In some further embodiments, the resin is a thermosetting resin. After curing, the thermosetting resin cross-links to form a three-dimensional network structure, making it less prone to deformation and softening during subsequent sintering, curing, and encapsulation processes in solar cell fabrication, such as encapsulation. Furthermore, the curing process hardly damages the already formed connection structure of the sintered copper particles, maintaining the integrity of the conductive pathways.

[0104] In some further embodiments, the resin is selected from at least one of phenolic resin, epoxy resin, polyester resin, vinyl resin, phthalate resin, oligonucleotide acrylate resin, xylene resin, bismuth triazine resin, polyurethane, melamine resin, silicone resin, acrylic resin, oxetane resin, and oxazine resin (i.e., benzoxazine resin).

[0105] From the perspective of improving adhesion to the battery substrate, the resin is preferably at least one of phenolic resin, epoxy resin, or unsaturated polyester resin.

[0106] In a further specific embodiment, the epoxy resin may be selected from one or more of bisphenol A type epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A type epoxy resin, polyurethane modified epoxy resin, dimer acid modified epoxy resin, siloxane modified epoxy resin, phenolic type epoxy resin, polyol glycidyl ether type epoxy resin, and polyacid glycidyl ester type epoxy resin. Of course, other resins known in the art that can be used in this application may also be selected, and this application does not further limit this choice.

[0107] In some embodiments, the resin content in the copper paste is 1-15% by mass. This improves adhesion to the battery substrate while maintaining good conductivity, avoiding the deterioration of the conductivity of the copper electrode caused by introducing too much insulating resin.

[0108] Optionally, the mass content of resin in the copper paste may be, for example, 1%, 3%, 5%, 7%, 9%, 11%, 13%, or 15%, or a range consisting of any two of the above values.

[0109] In some embodiments, the dispersion medium further includes a solvent, which may be selected from at least one of water, ester compounds, ether compounds, and ketone compounds. For example, the solvent may be one or more of water, methanol, ethanol, propanol, isopropanol, butanol, isobutanol, hexanol, cyclohexanol, cyclohexanone, cyclohexanol, terpineol, ethylene glycol, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, diethylene glycol, ethylene glycol monoethyl ether acetate, and diethylene glycol monobutyl ether acetate.

[0110] For copper paste used in subsequent printing, from the viewpoint of making the viscosity range appropriate, the mass percentage of solvent in the copper paste is 1 to 10%.

[0111] Optionally, the mass content of the solvent may be, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%, or a range consisting of any two of the above values.

[0112] In some embodiments, the dispersion medium further includes a curing agent. The curing agent may be one or more selected from dicyandiamide curing agents, tertiary amine curing agents, isocyanates, imidazole curing agents, acid anhydride curing agents, and latent imidazole curing agents, such as triethanolamine, blocked isocyanates, 1-butyl-3-methylimidazolium dibutyl phosphate, and Busington (Lanxess) 7982. Isocyanates are selected from one or more selected from Trixene BI 7982 (a blocked isocyanate based on HDI), MF-K60X (a blocked polyisocyanate HDI curing agent), ketoxime-terminated isocyanates, hexamethylene diisocyanate-terminated with hexamethylene hexamethylene diisocyanate, and dodecyl mercaptan-terminated diphenyl diisocyanate. Of course, other curing agents known in the art that can be used in this application may also be selected, and this application does not further limit their use.

[0113] In some embodiments, the dispersion medium further includes a dispersant. The dispersant may be an ether, amine, carboxylic acid, or other dispersant having 16-20 carbon atoms with an amino group at the end or a polar group such as a hydroxyl group, for example, Tween, OP series, oleic acid, and Span dispersants. Of course, other dispersants known in the art that can be used in this application may also be selected, and this application does not further limit their use.

[0114] In some embodiments, the dispersion medium may or may not contain a curing accelerator. The curing accelerator catalyzes the curing of the resin, lowers the curing temperature, and shortens the curing time. The curing accelerator may be selected from quaternary ammonium salts, imidazole esters or imidazoleonium salts, or substituted ureas. Specifically, quaternary ammonium salts can be benzyltriethylammonium chloride, etc., and substituted ureas can be N-p-chlorophenyl-N,N'-dimethylurea, N-(3,4-dichlorophenyl)-N,N'-dimethylurea, N-(3-phenyl)-N,N'-dimethylurea, N-(4-phenyl)-N,N'-dimethylurea, 2-methylimidazolium, etc.; imidazoles and their esters or imidazolium salts can be imidazolium sulfonate / salt, imidazolium phosphate / salt, or imidazolium acetate / salt, such as imidazolium dibutyl phosphate, 1-ethyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium methane sulfonate, trimellitate 1-cyanoethyl-2-undecapidazolium, isocyanurate 2-methylimidazolium, tetraphenylboronic acid 2-ethyl-4-methylimidazolium, and tetraphenylboronic acid 2-ethyl-1,4-dimethylimidazolium.

[0115] As an example, the method for preparing the copper paste in this application may include the following steps A to B.

[0116] In step A, a plurality of first conductive copper particles with an average particle size of 1 to 10 μm and a plurality of second conductive copper particles with an average particle size of 50 to 300 nm are provided.

[0117] In step B, multiple first conductive copper particles, multiple second conductive copper particles, resin, solvent, curing agent and dispersant are mixed in a certain proportion and then ground by a three-roll mill.

[0118] According to another embodiment of this application, an electrode is provided, including a transport electrode, wherein the transport electrode is a copper electrode. Figure 4 A scanning electron microscope image of a cross-section of a copper electrode according to an embodiment of this application is shown; Figure 5 A scanning electron microscope image of a cross-section of a copper electrode according to another embodiment of this application is shown; Figure 6 A partial transmission electron microscope (TEM) image of a cross-section of a copper electrode according to an embodiment of this application is shown. Figures 4-6As shown, the copper electrode includes multiple third conductive copper particles 3 and multiple fourth conductive copper particles 4; the average particle size of the multiple third conductive copper particles 3 is 1~10μm, the average particle size of the multiple fourth conductive copper particles 4 is 50~400nm, and the shape of the third conductive copper particles 3 is a polyhedron; at least some of the adjacent fourth conductive copper particles 4 have an overlap portion 5, and the adjacent fourth conductive copper particles 4 are connected through the overlap portion 5.

[0119] In this application, the third conductive copper particle 3 can be understood as being formed after the first conductive copper particle 1 in the copper paste has been sintered and solidified. The fourth conductive copper particle 4 can be understood as being formed after the second conductive copper particle 2 in the copper paste has been sintered and solidified.

[0120] According to embodiments of this application, the third conductive copper particle 3 and the fourth conductive copper particle 4 are fused and recrystallized together, increasing the contact area between multiple conductive copper particles during sintering. The combination of particles with micron and nanometer-sized diameters promotes densification among the conductive copper particles, further reducing their line resistance and thus improving the conductivity of the copper electrode. By fusion and interconnecting the smaller fourth conductive copper particles 4 to form overlapping portions 5, more conductive pathways are provided, further reducing the line resistance of the copper electrode. Furthermore, the polyhedral shape of the third conductive copper particle 3, compared to a spherical structure, provides a larger contact area with the fourth conductive copper particle 4 and provides a supporting framework, improving the stability of the copper electrode, preventing collapse, and contributing to a higher aspect ratio.

[0121] It should be noted that, after sintering, the difference between the microstructure of the third conductive copper particle 3 and the first conductive copper particle 1 is less obvious than the difference between the microstructure of the fourth conductive copper particle 4 and the second conductive copper particle 2.

[0122] In particular, when the second conductive copper particle 2 is copper hydride, due to the reducing properties of copper hydride, it is less likely to be oxidized than elemental copper when placed in air. Furthermore, during the initial heating and drying process, for example, at temperatures between 60 and 100°C, copper hydride can decompose to form elemental copper.

[0123] Alternatively, if the second conductive copper particle 2 is elemental copper with a copper oxide coating layer on its surface, and the outer surface of the copper oxide coating layer is coated with a hypophosphite compound, the copper oxide and the hypophosphite compound react with each other to generate copper hydride, which is then further decomposed into elemental copper under heating conditions.

[0124] Optionally, the copper hydride in the fourth conductive copper particle 4 can be partially or completely converted into elemental copper. Preferably, Figure 7 It shows the relationship with Figure 6 Elemental analysis diagrams at the same locations. For example... Figure 7As shown, in the copper electrode, all the copper elements in the fourth conductive copper particle 4 exist in the form of elemental copper.

[0125] Optionally, the average particle size of the third conductive copper particle 3 can be, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, or a range consisting of any two of the above values.

[0126] Optionally, the average particle size of the fourth conductive copper particle 4 can be, for example, 50nm, 70nm, 100nm, 120nm, 150nm, 170nm, 200nm, 230nm, 250nm, 270nm, 290nm, 310nm, 330nm, 350nm, 370nm or 400nm, or a range consisting of any two of the above values.

[0127] The method for measuring the average particle size of the third conductive copper particle 3 and the fourth conductive copper particle 4 is the same as described above and will not be repeated here. Furthermore, the method for measuring the aspect ratio of the irregular third conductive copper particle 3 is the same as that of the first conductive copper particle 1 and will not be repeated here.

[0128] It should be noted that the shapes of the conductive copper particles of different sizes, as well as the materials and amounts of the dispersion medium used, are largely the same as those mentioned above, and will not be repeated here.

[0129] In some further embodiments, the average particle size of the third conductive copper particles is 1~5μm. The more uniform particle size is more conducive to improving the packing density of the conductive particles in the copper electrode together with the fourth conductive copper particles 4, further reducing the line resistance.

[0130] Figure 8 A top-view scanning electron microscope image of a copper electrode according to an embodiment of this application is shown; Figure 9 A scanning electron microscope image of a cross-section of a copper electrode according to another embodiment of this application is shown; Figure 10 A transmission electron microscope (TEM) image of a cross-section of a copper electrode according to an embodiment of this application is shown. Figures 8-10 As shown, by combining conductive copper particles of different sizes, the packing density of the conductive copper particles is further improved, thus enhancing the conductivity.

[0131] In some further implementations, such as Figure 4 , Figure 10As shown in the frame, adjacent third conductive copper particles 3 and / or fourth conductive copper particles 4 are connected through surface contact or bulk contact. Surface contact or bulk contact effectively establishes a tight interconnection between the conductive copper particles, forming more and more unobstructed conductive transport channels. This helps eliminate oxide layers and interface barriers between conductive copper particles, thus reducing the obstruction to electron transport between them. Larger particles can then form conductive pathways through smaller particles, effectively reducing the line resistance of the copper electrode and further improving its conductivity.

[0132] In some implementations, such as Figure 4 As shown, the third conductive copper particle 3 and the fourth conductive copper particle 4 can be connected by surface contact or body contact. In this case, one fourth conductive copper particle 4 can be connected to one third conductive copper particle 3, or multiple fourth conductive copper particles 4 can be connected to one third conductive copper particle 3. This application does not make any special limitation on the number of connected fourth conductive copper particles 4.

[0133] In other embodiments, adjacent third conductive copper particles 3 may be connected by surface contact or body contact. In still other embodiments, adjacent fourth conductive copper particles 4 may be connected by at least surface contact or body contact, in which case adjacent fourth conductive copper particles 4 may be connected to each other by overlapping portions 5.

[0134] It is understood that this application does not require all three of the above conditions to exist simultaneously. For example, it is permissible for only adjacent fourth conductive copper particles 4 to be connected via surface contact or body contact. Preferably, adjacent fourth conductive copper particles 4 are connected via surface contact or body contact, and the third conductive copper particle 3 is connected to the adjacent fourth conductive copper particle 4 via surface contact or body contact. This further widens the conductive path and further reduces the line resistance of the copper electrode. Of course, in addition to surface contact and body contact, adjacent third conductive copper particles 3 and / or fourth conductive copper particles 4 can also be connected via point contact or line contact.

[0135] In some implementations, such as Figure 8As shown, the surface of the third conductive copper particle 3 has at least one first microstructure 31, which is recessed towards the interior of the third conductive copper particle 3. A portion of the fourth conductive copper particle 4 is located within the first microstructure 31. The first microstructure 31 is located on the surface of a portion of the third conductive copper particle 3, and the edge of the first microstructure 31 can be spherical. The first microstructure 31 can be arranged regularly or irregularly, at least on the third conductive copper particle 3. Here, "the edge is spherical" can be understood as the edge contour of the first microstructure 31 being spherical. For example, when the first microstructure 31 is cut in a direction perpendicular to the surface of the third conductive copper particle 3, the connection area between the first microstructure 31 and the surface of the third conductive copper particle 3 can be an arc-shaped surface with continuously changing curvature. Its curvature characteristics can be close to the surface formed by the intersection of the side of a sphere or a quasi-sphere (e.g., an ellipsoid) and a plane, or it can be an arc-shaped surface formed by the fusion of multiple spheres. The presence of the first microstructure 31 helps to increase the effective conductive contact area. The fourth conductive copper particle 4 is located in the first microstructure 31, which further increases the conductive contact area and reduces the volume resistance inside the copper electrode, thereby improving the conductivity uniformity of the copper electrode.

[0136] In some embodiments, the copper electrode is prepared by sintering and curing a copper paste as described above.

[0137] Copper paste can be formed on a battery substrate by printing, such as screen printing, inkjet printing, or laser transfer, with screen printing being a more cost-effective option. The following exemplifies the process of preparing a copper electrode by screen printing: preparing copper paste; using a screen template with a specific pattern to define the position and shape of the copper electrode; pressing the copper paste onto the surface of the battery substrate through the screen template to form a patterned structure of the copper electrode; and achieving good contact between the copper electrode and the battery substrate through sintering and curing.

[0138] As an example, sintering and curing may include the following steps: heating and curing a patterned copper paste in a nitrogen atmosphere to obtain a copper electrode. The curing temperature can be 250~350℃, for example, 250℃, 260℃, 270℃, 280℃, 290℃, 300℃, 310℃, 320℃, 330℃, 340℃, or 350℃. The curing time can be 1s~30min, for example, 1s, 3s, 5s, 10s, 30s, 1min, 3min, 6min, 9min, 12min, 15min, 18min, 21min, 24min, 27min, 30min, etc.

[0139] In some embodiments, the electrode further includes a contact electrode, which is electrically connected to the transmission electrode; the material of the contact electrode includes at least one of metal, metal oxide, metal nitride, metal carbide, metal sulfide, or conductive carbon material.

[0140] Specifically, the metal can be, for example, silver, copper, silver-plated copper, aluminum, nickel, gold, zinc, tin, lead, or alloys of the above metals; the metal oxide can be, for example, ITO, AZO, IWO, etc.; the metal nitride can be, for example, titanium nitride; the metal carbide can be, for example, titanium carbide; and the conductive carbon material can be, for example, graphene.

[0141] In some preferred embodiments, the contact electrode is made of metallic silver, and a transport electrode is located on the contact electrode. The contact electrode includes multiple first silver particles and multiple second silver particles. The average particle size of the multiple first silver particles is 1~10 μm, and the average particle size of the multiple second silver particles is 0.05~0.5 μm. This forms a uniform and continuous contact interface on the polycrystalline silicon substrate surface with the silver contact electrode layer, avoiding current concentration caused by localized voids or microcracks, thus helping to reduce contact resistance and improve carrier collection capability. The dual-size silver particles can form a uniform Ag-Si alloy layer with the polycrystalline silicon substrate during sintering, ensuring good ohmic contact while preventing excessive burn-through of the polycrystalline silicon layer by the silver contact electrode layer, which could damage the passivation structure.

[0142] It should be noted that the silver contact electrode can be either convex or concave, pointing away from the battery substrate. When screen-printed and then sintered, the resulting silver contact electrode is convex; when laser grooving or etching is used to create holes, the resulting silver contact electrode is concave. The shape of the transport electrode should be adapted to match the silver contact electrode during fabrication. Figure 11 It shows the relationship with Figure 10 Elemental analysis diagrams at the same locations; Figure 12 An elemental analysis diagram of a cross-section of the contact electrode according to an embodiment of this application is shown. Figure 11 The diagram illustrates that the main component of the transmission electrode is elemental copper, such as... Figure 12 As shown, the main component of the silver contact electrode is elemental silver, and the metal distribution and shape of the contact electrode and the transmission electrode are compatible with each other.

[0143] According to another aspect of this application, a solar cell is provided, including a cell body and electrodes, the electrodes being located on at least one surface of the cell body, the electrodes including the electrodes described above.

[0144] The battery body includes at least a substrate and a doped semiconductor layer on the battery substrate, wherein the substrate can be rectangular or square.

[0145] The substrate material can be silicon (Si), germanium (Ge), gallium arsenide (GaAs), etc. Obviously, in terms of conductivity type, the substrate can be an intrinsic semiconductor substrate, an n-type semiconductor substrate, or a p-type semiconductor substrate.

[0146] Optionally, the material of the doped conductive layer may include at least one semiconductor material selected from monocrystalline silicon, amorphous silicon, polycrystalline silicon, microcrystalline silicon, etc. In some embodiments, the doped conductive layer may be deposited on the surface of the substrate by a chemical vapor deposition process, while in other embodiments, the doped conductive layer may be obtained within the surface of the substrate by a doping process.

[0147] The passivation or antireflection layer is located on the surface of the doped conductive layer away from the substrate. The passivation or antireflection layer can simultaneously protect and passivate the underlying substrate or functional layer, such as a P-type or N-type doped conductive layer, as well as reduce the reflection of incident light. Exemplarily, the passivation or antireflection layer can be a single-layer film formed of silicon dioxide, aluminum oxide, silicon nitride, or silicon oxynitride, or a multilayer film composed of one or more of the aforementioned materials.

[0148] Optionally, the solar cell may further include an interface passivation layer located between the substrate and the doped conductive layer, for selectively allowing charge carriers to pass through and achieving a field passivation effect, thereby improving carrier separation and collection efficiency. Exemplarily, the interface passivation layer may be made of alumina, silicon oxide, titanium oxide, etc., and may form a tunneling oxide passivation contact (TOPCon) structure with the doped conductive layer.

[0149] Here, the above-described stacked structure is suitable for selectively transporting charge carriers such as electrons or holes. The stacked structure can be disposed on the entire surface of the substrate, with the corresponding doped conductive layers disposed on the entire surface of the substrate, but it is not limited to this. The stacked structure can also be disposed only on a portion of the surface of the substrate, with the corresponding doped conductive layers arranged at intervals on the surface of the substrate.

[0150] In some embodiments, the solar cell is selected from any one of a back contact cell, a heterojunction cell, or a tunnel oxide passivated contact cell.

[0151] Taking a back-contact battery as an example, Figure 13 A schematic diagram of the structure of a solar cell according to an embodiment of this application is shown, as follows: Figure 13As shown, the electrode may include multiple first electrodes 210 and multiple second electrodes 220. The first electrodes 210 and second electrodes 220 can be current collector electrodes. Current collector electrodes are suitable for connecting current-collecting structures, such as current-collecting electrodes or solder strips, or other current-collecting structures. When welding other current-collecting structures onto the current collector electrodes or current-collecting electrodes, the direction of the welding force is inconsistent with the extension direction of the linear protrusions, which helps to disperse stress, thereby improving the mechanical strength of the battery and reducing the likelihood of battery cracking. The first electrode 210 can be a copper electrode prepared from the aforementioned copper paste, and the second electrode 220 can also be a copper electrode prepared from the aforementioned copper paste, or arbitrarily selected from Ag, Al, Ni, Au, Zn, Sn, Pb, or any combination thereof. This combination based on the size of two copper particles helps to expand the conductive path, reduce the line resistance of the electrode, and improve conductivity.

[0152] The electrode also includes a first silver electrode 230 and a second silver electrode 240, further forming a uniform and continuous contact interface, with the first electrode 210 located on the first silver electrode 230 and the second electrode 220 located on the second silver electrode 240.

[0153] The substrate 100 includes a first surface 101a and a second surface 101b. The first surface 101a may be, for example, the light-receiving surface of the substrate, and the second surface 101b may be, for example, the backlight surface of the substrate.

[0154] The doped conductive layer includes a first doped conductive layer 1021 and a second doped conductive layer 1022. Both the first doped conductive layer 1021 and the second doped conductive layer 1022 are located on the second surface 101b of the substrate 100 and are arranged alternately.

[0155] The passivation or antireflection layer includes a first passivation or antireflection layer 1041 and a second passivation or antireflection layer 1042. The first passivation or antireflection layer 1041 is located on the surface of the first doped conductive layer 1021 away from the substrate 100, and the second passivation or antireflection layer 1042 is located on the surface of the second doped conductive layer 1022 away from the substrate 100.

[0156] The interface passivation layer includes a first interface passivation layer 1031 and a second interface passivation layer 1032. The first interface passivation layer 1031 is located between the first doped conductive layer 1021 and the second surface 101b of the substrate 100, and the second interface passivation layer 1032 is located between the second doped conductive layer 1022 and the second surface 101b of the substrate 100.

[0157] It is understood that there is an isolation region (gap) between the first doped conductive layer 1021 and the second doped conductive layer 1022.

[0158] Taking bi-sided batteries as an example, Figure 14A schematic diagram of the structure of a solar cell according to another embodiment of this application is shown, as follows: Figure 14 As shown, the main difference from the aforementioned back-contact battery is that a stacked structure covers the entire first surface 101a, comprising a first doped conductive layer 1021 and a first passivation or antireflection layer 1041, with the first passivation or antireflection layer 1041 located on the surface of the first doped conductive layer 1021 away from the substrate 100. Another stacked structure is disposed entirely on the second surface 101b, comprising a second doped conductive layer 1022 and a second passivation or antireflection layer 1042, with the second passivation or antireflection layer 1042 located on the surface of the second doped conductive layer 1022 away from the substrate 100.

[0159] One of the first doped conductive layer 1021 and the second doped conductive layer 1022 may be an N-type doped polysilicon layer, and the other may be a P-type doped polysilicon layer. The doped conductive layer can form a poly-finger structure with the electrode 200.

[0160] According to some embodiments of this application, the stacked structure located on the first surface 101a may further include a first interface passivation layer 1031, which is located between the first surface 101a of the substrate 100 and the first doped semiconductor layer 1031. The stacked structure located on the second surface 101b may further include a second interface passivation layer 1032, which is located between the second surface 101b of the substrate 100 and the second doped semiconductor layer 1032.

[0161] According to another embodiment of this application, a photovoltaic module is provided, including a plurality of solar cells as described above, and a plurality of electrical connection lines electrically connecting adjacent solar cells.

[0162] According to an embodiment of this application, the above-mentioned solar cells are connected in series to form a solar cell string; and an encapsulation structure is disposed around the outer periphery of the solar cell string.

[0163] According to embodiments of this application, the number of solar cells connected in series can be 4 to 80, for example, 4, 24, 54, 72, or 78 cells. Multiple solar cells can form several solar cell strings, with the cells within each string connected in series. The solar cell strings can be connected in series or in parallel, and are connected to each other via busbars.

[0164] According to embodiments of this application, the encapsulation layer may include a backsheet, an encapsulating film, a glass panel, etc., to improve the stability of the solar cell string. The glass panel is located on the front of the solar cell string, and the backsheet is located on the back of the solar cell string, both serving a protective function. The adhesive film is an adhesive film between the solar cell and the glass panel and backsheet, serving a bonding and fixing function, and can be made of a transparent material.

[0165] The present application is further illustrated below through embodiments, accompanying drawings, and related test experiments and results. In the following detailed description, numerous specific details are set forth for ease of explanation to provide a comprehensive understanding of the embodiments of the present application. However, it is apparent that one or more embodiments may be implemented without these specific details. Moreover, the details in the following embodiments can be arbitrarily combined to form other feasible embodiments without conflict.

[0166] It should be noted that the specific embodiments described below are merely illustrative examples, and the scope of protection of this application is not limited thereto. The chemicals and raw materials used in the following embodiments are all commercially available or prepared using recognized processing methods.

[0167] Example 1:

[0168] The preparation process of copper paste:

[0169] Prepare 8g of copper powder, which includes a mixture of large, irregularly shaped polyhedral first conductive copper particles and small, spherical second conductive copper particles in a mass ratio of 1:1. The ratio of the maximum distance to the minimum distance between the opposite ends of the first conductive copper particles is 2.5:1. Both the first and second conductive copper particles are composed of elemental copper. The average particle size of the first conductive copper particles is 3μm, and the average particle size of the second conductive copper particles is 100nm. Both the first and second conductive copper particles are coated with dodecylamine.

[0170] 0.4g of bisphenol F epoxy resin, 0.15g of curing agent dicyandiamide, 0.2g of 2-propylimidazolium, 0.05g of dispersant oleic acid, and 0.3g of solvent diethylene glycol butyl ether acetate were stirred evenly in a petri dish to obtain a slurry mother liquor. 8g of copper powder was poured into the slurry mother liquor and stirred. The mixture was then poured into a three-roll mill for rolling and grinding to obtain a homogeneous copper paste.

[0171] The dried copper paste was observed using a scanning electron microscope (SEM), and the resulting SEM image is shown below. Figures 1-3 As shown, the first conductive copper particle has an irregular polyhedral shape, and at least a portion of the surface of the first conductive copper particle is non-planar. Some of the surface of the first conductive copper particle has depressions, and some of the second conductive copper particles are located in the depressions.

[0172] Transmission electron microscopy revealed that a copper oxide layer also existed on the surface of the first and second conductive copper particles within the organic coating layer formed by dodecylamine.

[0173] Preparation of copper electrode: Silver paste is printed on the battery substrate and sintered to obtain the contact electrode. Then, copper paste is printed onto the contact electrode by screen printing and cured by heating in a curing device at a curing temperature of 300℃ for 3s. After sintering and curing, a 1cm×1cm square copper electrode is obtained.

[0174] The obtained copper electrode was observed using a scanning electron microscope (SEM), and the resulting SEM image is shown below. Figures 4-6 As shown, it is understandable. Figures 4-6 , Figure 8 , Figures 9-10 These are scanning electron microscope (SEM) images of different cross-sections of the copper electrode. Figures 4-6 , Figures 9-10 As shown, some of the fourth conductive copper particles are electrically connected to the third conductive copper particles, and adjacent fourth conductive copper particles are connected through overlapping portions, or adjacent third conductive copper particles and fourth conductive copper particles are connected through surface contact or body contact. Figure 8 As can be seen from the diagram, after sintering, the first conductive copper particle forms a first microstructure with a recessed surface, forming a third conductive copper particle. At this time, a portion of the fourth conductive copper particle is located within the first microstructure.

[0175] The formed copper electrode was observed using a transmission electron microscope and elemental analysis was performed. The results are as follows: Figure 7 , Figure 11 As shown, it can be confirmed that the main component of the third and fourth conductive copper particles after sintering and solidification is copper.

[0176] Example 2:

[0177] The preparation process of Example 2 is largely the same as that of Example 1, except that different specifications of copper powder are used. The mixture includes large, irregularly shaped polyhedral first conductive copper particles and small, spherical second conductive copper particles in a mass ratio of 1:1. Both the first and second conductive copper particles are composed of elemental copper. The average particle size of the first conductive copper particles is 7 μm, and the ratio between the maximum and minimum distances between the opposite ends of the first conductive copper particles is 2:1. The average particle size of the second conductive copper particles is 300 nm. The surface of the first conductive copper particles is coated with dodecylamine, and the surface of the second conductive copper particles is coated with copper hydride.

[0178] Transmission electron microscopy revealed that a copper oxide layer also existed on the surface of the first conductive copper particle within the organic coating layer formed by dodecylamine.

[0179] The copper electrode was prepared using a method largely the same as that used in Example 1.

[0180] Comparative Example 1:

[0181] The preparation process of Comparative Example 1 is largely the same as that of Example 1, except that different specifications of copper powder were replaced. Only the large, irregularly shaped first conductive copper particles were retained, and the surface of the first conductive copper particles was coated with a dodecylamine coating layer. The average particle size of the first conductive copper particles was 3 μm. The copper electrode was prepared in a manner largely the same as that of Example 1.

[0182] Comparative Example 2:

[0183] The preparation process of Comparative Example 2 is largely the same as that of Example 2, except that different specifications of copper powder were replaced. Only small spherical second conductive copper particles were retained. The surface of the second conductive copper particles is coated with a copper hydride coating layer. The average particle size of the second conductive copper particles is 300 nm. Their specific specifications are shown in Table 1 below. The copper electrode was prepared in a manner largely the same as that of Example 1.

[0184] Comparative Example 3:

[0185] The preparation process of Comparative Example 3 is largely the same as that of Example 1, except that different specifications of copper powder are used. The copper powder includes spherical or near-spherical first conductive copper particles and spherical or near-spherical second conductive copper particles. The average particle size of the first conductive copper particles is 3 μm, and the average particle size of the second conductive copper particles is 100 nm. The surfaces of the first and second conductive copper particles are coated with dodecylamine.

[0186] The copper electrodes prepared in Examples 1-2 and Comparative Examples 1-2 were subjected to electrical performance tests. The line resistance of the formed copper electrodes was tested, and the sheet resistance of the sintered copper electrodes was tested using the four-point probe method. At least five different test points were selected on the same copper electrode for measurement, and the arithmetic mean was taken as the sheet resistance value of the copper electrode (unit: mΩ / □). The resistance was then calculated according to the formula R... line =R s The line resistance R is obtained by converting × (L / W). line (Unit: Ω). Where R s Where L is the sheet resistance, W is the length of the copper electrode, and L is the width of the copper electrode.

[0187] The power decay of the aforementioned copper electrodes was tested after 1000 hours of aging. This was conducted under standard test conditions (25℃, 1000 W / m). 2Under irradiance, the initial maximum output power (P0) of each assembled component was measured. Examples 1-2 and Comparative Examples 1-2 were placed in an environmental test chamber using the same method and kept at 85℃±2℃ and 85%±5% relative humidity for 1000 hours. They were then placed again under standard test conditions (25℃, 1000W / m²). 2 Under irradiance conditions, the maximum output power (P1) of each assembled component was tested. The power attenuation rate was calculated using the following formula:

[0188] Power attenuation rate = [(P0-P1) / P0] × 100%.

[0189] Table 1

[0190]

[0191] A comparison of Examples 1-2 and Comparative Examples 1-2 shows that by using relatively small second conductive copper particles to fill the gaps between the first conductive copper particles that form the framework, the sintered result can achieve the desired effect. Figure 6 The formation of an effective sintering neck significantly reduces line resistance. The use of near-spherical second conductive copper particles provides a rolling effect, optimizes rheology, reduces printing tailing, and facilitates the printing of finer copper electrodes. Furthermore, the shape of the first conductive copper particles helps to expand the conductive interface and reduce line resistance. This application, by blending two types of conductive copper particles with different average particle sizes, can slow down oxidation at room temperature, and the optimized ratio reduces sintering shrinkage stress, improves stability and adhesion to the battery substrate, and reduces the power decay rate after 1000 hours of aging.

[0192] Comparing the results of Example 1 and Comparative Example 3, it can be seen that although Comparative Example 3 uses a blend of large-diameter and small-diameter conductive copper particles, all of them are spherical conductive copper particles. After curing in a short time, the conductive copper particles may still have spherical point contact, and the contact area is much smaller than the surface contact / edge contact of irregular polyhedral particles. This results in insufficient expansion of the conductive interface and poor overall compactness of the copper electrode. The line resistance and attenuation performance are inferior to those of Example 1.

[0193] Example 3:

[0194] The preparation process of Example 3 is largely the same as that of Example 1, except that the main component of the second conductive copper particle is copper hydride. After testing the performance of the prepared copper electrode, it was found that it has a line resistance and a power decay rate after 1000 hours of aging that are comparable to those of Example 1.

[0195] Example 4:

[0196] The preparation process of Example 4 is largely the same as that of Example 1, except that the surface of the second conductive copper particle is coated with hypophosphite. After testing the performance of the prepared copper electrode, it was found that it has a line resistance and a power decay rate after 1000 hours of aging that are comparable to those of Example 1.

[0197] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of this application. It should be understood that the above descriptions are merely specific embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A copper paste, comprising: Copper powder and dispersion medium; the copper powder comprises a plurality of first conductive copper particles and a plurality of second conductive copper particles; The average particle size of the plurality of first conductive copper particles is 1~10μm, the average particle size of the plurality of second conductive copper particles is 50~300nm, and the shape of the first conductive copper particles is a polyhedron.

2. The copper paste according to claim 1, wherein, The average particle size of the plurality of the first conductive copper particles is 2~5μm.

3. The copper paste according to claim 1, wherein, The first conductive copper particle has an irregular polyhedral shape.

4. The copper paste according to claim 3, wherein, The ratio of the maximum distance to the minimum distance between the two opposite ends of the first conductive copper particle is (1~3):

1.

5. The copper paste according to any one of claims 1 to 4, wherein, At least one surface of the first conductive copper particle is non-planar; Preferably, at least one of the surfaces has a first texture structure.

6. The copper paste according to any one of claims 1 to 5, wherein, The second conductive copper particle is a sphere or a near-sphere; and / or, D of multiple second conductive copper particles 95 Particle size and D 50 The ratio of particle size to particle size is <3; and / or, The surface of the second conductive copper particle has a second texture structure.

7. The copper paste according to any one of claims 1 to 6, wherein, The first conductive copper particle and / or the second conductive copper particle are composed of elemental copper.

8. The copper paste according to claim 7, wherein, The surfaces of the first conductive copper particle and / or the second conductive copper particle are sequentially coated with a first coating layer and a second coating layer from the inside out. The first coating layer is composed of copper oxide, and the second coating layer is composed of at least one of organic matter, copper hydride, or hypophosphite compounds.

9. The copper paste according to claim 6, wherein, The second conductive copper particle is composed of copper hydride.

10. The copper paste according to any one of claims 1 to 9, wherein, The mass ratio of the first conductive copper particle to the second conductive copper particle is (0.5~10):

1.

11. The copper paste according to any one of claims 1 to 10, wherein, The dispersion medium includes a resin, a curing agent, a dispersant, and a solvent; Preferably, the resin is a thermosetting resin; More preferably, the resin is selected from at least one of phenolic resin, epoxy resin, polyester resin, vinyl resin, phthalate resin, oligonucleotide acrylate resin, xylene resin, bismuth triazine resin, polyurethane, melamine resin, silicone resin, acrylic resin, oxetane resin, and oxazine resin.

12. An electrode, comprising a transport electrode, wherein the transport electrode is a copper electrode, and the copper electrode comprises a plurality of third conductive copper particles and a plurality of fourth conductive copper particles; in, The average particle size of the plurality of third conductive copper particles is 1~10μm, preferably 1~5μm, and the average particle size of the plurality of fourth conductive copper particles is 50~400nm. The shape of the third conductive copper particles is a polyhedron. In this configuration, at least some of the adjacent fourth conductive copper particles have an overlap portion, and the adjacent fourth conductive copper particles are connected through the overlap portion.

13. The electrode according to claim 12, wherein, The adjacent third conductive copper particles and / or fourth conductive copper particles are connected by surface contact or body contact.

14. The electrode according to claim 12 or 13, wherein, The surface of the third conductive copper particle has at least one first microstructure, the first microstructure being recessed toward the interior of the third conductive copper particle, and a portion of the fourth conductive copper particle is located within the first microstructure.

15. The electrode according to any one of claims 12 to 14, wherein, The copper electrode is prepared using the copper paste according to any one of claims 1 to 12.

16. The electrode according to any one of claims 12 to 14, wherein, The electrode further includes a contact electrode, which is electrically connected to the transmission electrode; The material of the contact electrode includes at least one of metal, metal oxide, metal nitride, metal carbide, metal sulfide, or conductive carbon material.

17. The electrode according to claim 16, wherein, The contact electrode is made of metallic silver and includes a plurality of first silver particles and a plurality of second silver particles. The average particle size of the plurality of first silver particles is 1 to 10 μm, and the average particle size of the plurality of second silver particles is 0.05 to 0.5 μm.

18. A solar cell comprising a cell body and an electrode located on at least one surface of the cell body, the electrode comprising the electrode as claimed in any one of claims 12 to 17.

19. The solar cell according to claim 18, wherein, The solar cell is selected from any one of back contact cells, heterojunction cells, and tunnel oxide passivated contact cells.

20. A photovoltaic module comprising a plurality of solar cells as described in claim 18 or 19, and a plurality of electrical connection lines electrically connecting adjacent solar cells.